2014
DOI: 10.7863/ultra.33.11.1909
|View full text |Cite
|
Sign up to set email alerts
|

Decidualized Endometrioma Masquerading as Ovarian Cancer in Pregnancy

Abstract: There were no characteristic sonographic features identified to distinguish decidualized endometrioma from ovarian malignancy. However, lesions showing no change in size over 4 weeks or lacking solid components and vascularity are more likely to be benign rather than malignant and may justify delaying surgery until delivery or postpartum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
4
0
2
Order By: Relevance
“…4 Another series of 17 cases also having surgery for DEs resembling a malignancy was reported, all of which had a benign result. 5 In contrast, a series of 24 cases which were expectantly managed during pregnancy for the sonographically described DEs appearing to be possibly malignant revealed the resolution of this decidualization at the conclusion of each pregnancy, serving to be reassuring for this expectant type of management. 6 Further commentary of the benefit of expectant management of pregnancy-related DEs was recently reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…4 Another series of 17 cases also having surgery for DEs resembling a malignancy was reported, all of which had a benign result. 5 In contrast, a series of 24 cases which were expectantly managed during pregnancy for the sonographically described DEs appearing to be possibly malignant revealed the resolution of this decidualization at the conclusion of each pregnancy, serving to be reassuring for this expectant type of management. 6 Further commentary of the benefit of expectant management of pregnancy-related DEs was recently reinforced.…”
Section: Discussionmentioning
confidence: 99%
“…DePriest and DeSimone reported that investigations with regard to blood flow on Doppler demonstrated that Doppler examination did not further facilitate diagnosis compared with gray-scale sonography alone, with a similar false-positive rate of 49% for the prediction of malignancy (6). Groszmann et al did not identify any morphological or vascular flow characteristics that were helpful in sonographically distinguishing benign decidualized endometrioma from malignancy (7).…”
Section: Discussionmentioning
confidence: 99%
“…Under the action of progesterone, hypertrophy of the endometrial stromal cells leads to cyst enlargement and irregular and vascular solid components, mimicking malignancy on imaging, potentially leading to unnecessary surgical intervention. Decidualized ovarian endometrioma in pregnancy is a rare condition and we only identify 18 studies comprising a total of 61 cases of ovarian decidualized endometriomas during pregnancy after the literature review [3,4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]. The main characteristics of the published cases are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 99%